2009
DOI: 10.2984/049.063.0306
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Movements of Hawksbill Turtles (Eretmochelys imbricata) from Nesting to Foraging Areas within the Hawaiian Islands

Abstract: Hawksbill sea turtles, Eretmochelys imbricata, reside around the main Hawaiian Islands but are not common. Flipper-tag recoveries and satellite tracking of hawksbills worldwide have shown variable distances in post-nesting travel, with migrations between nesting beaches and foraging areas ranging from 35 to 2,425 km. Nine hawksbill turtles were tracked within the Hawaiian Islands using satellite telemetry. Turtles traveled distances ranging from 90 to 345 km and took between 5 to 18 days to complete the transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…While hawksbill nonmigra tory behavior has previously been documented for individuals inhabiting archipelagos (e.g. Mortimer & Balazs 1999, Parker et al 2009), our research provides the first clear evidence that adult female hawksbills occupying mainland coasts can also be non-migratory. While there are biological benefits to remaining in close proximity to nesting beaches after completing the nesting cycle, e.g.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…While hawksbill nonmigra tory behavior has previously been documented for individuals inhabiting archipelagos (e.g. Mortimer & Balazs 1999, Parker et al 2009), our research provides the first clear evidence that adult female hawksbills occupying mainland coasts can also be non-migratory. While there are biological benefits to remaining in close proximity to nesting beaches after completing the nesting cycle, e.g.…”
Section: Discussionsupporting
confidence: 53%
“…comm.). Further research into hawksbill diet is of particular interest both from biological and conservation perspectives, particularly given the small average size of the adult female hawksbills in the present study (Horrocks et al 2001, Troëng et al 2005, Cuevas et al 2008, Parker et al 2009). …”
Section: Discussionmentioning
confidence: 92%
“…The few studies estimating home ranges for juvenile hawksbills have generally found areas of 1 km 2 or less (0.07 to 0.14 km ), while 2 larger individuals had home ranges of 2.6 km 2 (48.5cm CCL) and 4.04 km 2 (50.8 cm CCL). Our core-use area estimate was substantially larger than most previously reported (~1 km 2 or less) home-range sizes for immature hawksbills and the 0.5 to 2.0 km 2 adult home-range estimate from Hawaii (Parker et al 2009 body size of sub-adults compared to juveniles, as the results of Scales et al (2011) suggest. As well, homerange size at DRTO may be larger than that for hawksbills at other sites simply due to DRTO-specific habitat configurations.…”
Section: Discussioncontrasting
confidence: 81%
“…Compared to home-range estimates for hawksbills tagged elsewhere and in different size-classes, our results show that the 3 turtles tagged at DRTO had core-use areas ranging from 9.2 to 21.5 km 2 . Previously reported home-range estimates for wild adult hawksbills were 2.0 to 49.5 km 2 in Barbados (Horrocks et al 2001) and 0.5 to 2.0 km 2 in Hawaii (Parker et al 2009); both of these estimates were determined using a minimum convex polygon (MCP) approach. The few studies estimating home ranges for juvenile hawksbills have generally found areas of 1 km 2 or less (0.07 to 0.14 km ), while 2 larger individuals had home ranges of 2.6 km 2 (48.5cm CCL) and 4.04 km 2 (50.8 cm CCL).…”
Section: Discussionmentioning
confidence: 99%
“…Published hawksbill migrations show that 11 of 13 females nesting in Maui and Hawaii islands return to nearby foraging grounds (Graham ; Parker et al. , ). For the two other tracked hawksbills, one stopped transmitting west of Kauai (Parker et al.…”
Section: Discussionmentioning
confidence: 99%